Assessment of choroidal blood flow using laser speckle flowgraphy - Calzetti, Giacomo (2020)
Background/aims There is considerable interest in novel techniques to quantify choroidal blood flow (CBF) in humans. In the present study, we investigated a novel technique to measure CBF based on laser speckle flowgraphy (LSFG) in healthy subjects. Methods This study included 31 eyes of 31 healthy, non-smoking subjects aged between 19 and 74 years. A commercial LSFG instrument was used to measure choroidal vessel diameter (CVD) and relative flow volume (RFV) in choroidal vessels that were identified on fundus photos, an approach that was used previously only for retinal vessels. The reproducibility and the effect of isometric exercise on these parameters were investigated. The latter was compared with measurement of subfoveal CBF using laser Doppler flowmetry (LDF). Results Intraclass correlation coefficients for CVD and RFV were higher than 0.8 indicating excellent reproducibility. During isometric exercise, we observed an increase in ocular perfusion pressure of approximately 60% (P<0.001). The increase in RFV and CBF was lower, but also highly significant versus baseline (at minute 6 of isometric exercise: RFV 10.5%±4.2%, CBF 8.3%±3.6%; P<0.001 each) indicating choroidal autoregulation. Conclusion LSFG may be a novel approach to study blood flow in choroidal vessels. Data are reproducible and show good agreement with LDF data.